2007
DOI: 10.1096/fasebj.21.5.a214-b
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in medical students

Abstract: Resilience in medical students. Introduction. Few studies of resilience in an academic atmosphere exist and that associate it as a factor of success or failure in their academic performance. The objective of the present work is to determine resilience in regular and repeating students of medicine during the first and second semester and to correlate it with academic performance. Methods. For the study two different groups of students were included, the first group was integrated by first year regular students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Some studies have reached values between 85.5% and 90% (Izunya et al, 2010;Mompeó Corredera, 2014) for this measure, and others just 15.8% (Dinsmore et al, 2001). The practice is perceived as satisfactory and students recommend it also as a way of learning anatomy (Robbins et al, 2009;Böckers et al, 2010;Bekele et al, 2011;Oyeyipo and Falana, 2012;Karau et al, 2014;Van Wyk and Rennie, 2015) (even in our case where the students have been trained in a digital environment), which is similar to data published elsewhere (Elizondo-Omaña et al, 2005;Azer and Eizenberg, 2007;Leboulanger, 2011;Qamar and Osama, 2014;Estai and Bunt, 2016). Also, up to 60% of the students suggested that the dissections offer a good opportunity to raise awareness and made them consider disease and death in more concrete sense, something that may not have happened had they not gone through this experience (Ellis, 2001;Aziz et al, 2002;Redwood and Townsend, 2011;Mompeó Corredera, 2014;Ghosh, 2017).…”
Section: Dissection Versus Other Learning Techniquessupporting
confidence: 84%
See 1 more Smart Citation
“…Some studies have reached values between 85.5% and 90% (Izunya et al, 2010;Mompeó Corredera, 2014) for this measure, and others just 15.8% (Dinsmore et al, 2001). The practice is perceived as satisfactory and students recommend it also as a way of learning anatomy (Robbins et al, 2009;Böckers et al, 2010;Bekele et al, 2011;Oyeyipo and Falana, 2012;Karau et al, 2014;Van Wyk and Rennie, 2015) (even in our case where the students have been trained in a digital environment), which is similar to data published elsewhere (Elizondo-Omaña et al, 2005;Azer and Eizenberg, 2007;Leboulanger, 2011;Qamar and Osama, 2014;Estai and Bunt, 2016). Also, up to 60% of the students suggested that the dissections offer a good opportunity to raise awareness and made them consider disease and death in more concrete sense, something that may not have happened had they not gone through this experience (Ellis, 2001;Aziz et al, 2002;Redwood and Townsend, 2011;Mompeó Corredera, 2014;Ghosh, 2017).…”
Section: Dissection Versus Other Learning Techniquessupporting
confidence: 84%
“…As well as reinforcing the theoretical aspects of their education, dissection also offers the student the opportunity to gain a better understanding of the human body. Working on a cadaver is undoubtedly a deeply emotional experience, but also one that allows students to develop the competence and coping skills that will be applied later in their professional careers (Marcos et al, 2004;Elizondo-Omaña et al, 2005;Böckers et al, 2010;Van Wyk and Rennie, 2015;Wilson et al, 2018).…”
Section: Dissection Versus Other Learning Techniquesmentioning
confidence: 99%
“…The notion of academic resilience or academic buoyancy [54] has been proffered to reflect a student's ability to successfully deal with educational setbacks, stress, and study pressures in schools (e.g., [55]). University students with high resilience report less psychological distress and elevated levels of perceived social support, campus connectedness, and academic achievement than their less resilient peers [56][57][58][59]. A relational form of resilience, adopted by female undergraduate students, has enabled them to deal with stress and is more facilitative for their subsequent academic performance than the resilience reported by male students [17,60,61].…”
Section: Resilience As a Model Trajectory In Higher Education (He)mentioning
confidence: 99%